Prevalência e fatores associados da síndrome de Osgood-Schlatter em uma amostra populacional de adolescentes brasileiros - Lucena, Gildasio Lucas de (2010)
Osgood-Schlatter (O-S) syndrome, a pathology of the musculoskeletal system, exhibits high incidence in adolescence, a phase of accelerated bone growth. Detection of physiopathological mechanisms that may cause disorders and dysfunctions in bone growth must be taken into account when planning physical activities, in order to promote normal physiological growth patterns. The aim of this epidemiological investigation was to identify and analyze the relationships between sociodemographic, anthropometric and clinical aspects and O-S. A cross-sectional design was used, with a representative sample of 956 subjects: 474 (49.6%) males and 482 (50.4%) females. Age range varied between 12 and 15 years (mean = 13.7±1.04). We used a battery of tests, previously applied in a pilot study, which met the aims of the investigation. Descriptive statistics (frequency, mean and standard deviation) were used and the odds ratio was calculated from bivariate and multivariate logistic regression (p<0.05). A prevalence of 9.8% was found (n = 94 cases): 11% males and 8.3% females. Hierarchized multivariate analysis showed a significant association between regular physical activities (OR= 1.94; CI 95%, 1.22-3.10) and shortening of the rectus femoris muscle (OR= 7.15; CI 95%, 2.86-17.86). The results may serve as a basis for therapeutic and prophylactic measures, in addition to increasing our knowledge of this syndrome in Brazilian adolescents. This investigation used a multidisciplinary approach, involving elements of anatomy, nutrition, physical education and physical therapy to elucidate the object under study related to Osgood-Schlatter syndrome